In silico and in vitro genotoxicity evaluation of descarboxyl levofloxacin, an impurity in levofloxacin. (July 2014) - Zhu, Qingfen; Li, Tao; Wei, Xia; Li, Jun; Wang, Weijian
Abstract It is important to establish the safety of impurities in drug substances or drug products. The assessment of genotoxicity of impurities and the determination of acceptable limits for genotoxic impurities was addressed in some recent guidances as a difficult issue. Descarboxyl levofloxacin is an impurity isolated from levofloxacin, which may impose a risk without associated benefit. However, there is insufficient toxic information about descarboxyl levofloxacin. This study investigated the genotoxicity of this impurity by in silico and in vitro methods. We used Derek, a commercial structure-activity relationship software package, as an in silico tool. The results showed that there was a structural alert (quinoline) in this impurity. Then, the in vitro genotoxicity of descarboxyl levofloxacin was investigated by a modified Ames test and by a chromosomal aberration test, using Chinese hamster lung (CHL) cells. Both assays were conducted in the presence or absence of S-9 mix. The results showed that the test impurity was not mutagenic in the Ames test (31.25–500 μg/plate). Whereas there was a statistically significant increase in the number of metaphase CHL cells with structural aberrations at the concentration of 1 mg/mL with S-9 mix, the aberrations rate was 7.5%. It did not significantly increase the number of structural aberration in CHL cells in the presence (at 250 and 500 μg/mL) or absence of S-9 mix. Based on these assays, descarboxyl levofloxacin could be controlled as a nongenotoxic impurity.